2007
DOI: 10.1017/s1751731107000699
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of offspring following supplementation of sow diets with oil during mid to late gestation

Abstract: This study aimed to determine the consequences of altering the fatty acid profile of sow diets during mid-to-late gestation; oils of different fatty acid composition were chosen as energy supplements to provide diets with different fatty acid profiles. Forty-eight multiparous sows were used to evaluate the effects of fat supplementation from day 60 of gestation until parturition. Sows were allocated to either 3 kg/day of commercial sow pellets (control; C) or an experimental diet consisting of 3 kg/day of comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
(25 reference statements)
4
2
0
Order By: Relevance
“…Other studies have also linked reduced fetal growth to placental insufficiency ( 22 , 37 , 42 ) . The increased weight at 21 d of age of the NBW offspring of FOG1 sows agrees with the results for average litter performance ( 21 , 38 ) and is in agreement with the findings of others ( 12 , 43 , 44 ) . It has previously been suggested that the improved performance of piglets born to oil-supplemented dams is as a result of improved piglet vigour at birth ( 12 , 45 ) ; it is speculated that improved vigour at birth may also be responsible for the improved growth performance of NBW FOG1 piglets in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Other studies have also linked reduced fetal growth to placental insufficiency ( 22 , 37 , 42 ) . The increased weight at 21 d of age of the NBW offspring of FOG1 sows agrees with the results for average litter performance ( 21 , 38 ) and is in agreement with the findings of others ( 12 , 43 , 44 ) . It has previously been suggested that the improved performance of piglets born to oil-supplemented dams is as a result of improved piglet vigour at birth ( 12 , 45 ) ; it is speculated that improved vigour at birth may also be responsible for the improved growth performance of NBW FOG1 piglets in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…It has previously been suggested that the improved performance of piglets born to oil-supplemented dams is as a result of improved piglet vigour at birth ( 12 , 45 ) ; it is speculated that improved vigour at birth may also be responsible for the improved growth performance of NBW FOG1 piglets in the current study. The increased weight at 21 d of age of NBW offspring, of EG2 sows, is in agreement with the results for whole litter performance ( 38 ) and suggests that the balance of energy to protein in maternal diets is important during the second half of gestation if piglet performance is to be maximized.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is possible that the number of piglets per litter born alive is not influenced by the addition of LSO (p > 0.05) because the death period of embryos occurs early, and therefore, the later addition of oil to the diet has no effect. Our results were similar to many reported (Rooke et al., ,b; Laws et al., , ), However, reports of the effects of dietary oil in sow diets on piglet performance are not consistent. Reports showed increasing fish oil in sow diets from 0% to 4% decreased piglet weaning weight and resulted in a higher pre‐weaning mortality rate (Rooke et al., ,b).…”
Section: Discussionsupporting
confidence: 88%
“…Due to the similarities in the fatty acid metabolism in human and pigs [21] and in order to test our hypothesis, this study aimed to determine the consequences of modifying the fatty acid composition of sows' diets, using dietary supplements with olive oil (OO) or fish oil (FO), during the first or the second half of gestation on the fatty acid profiles of maternal plasma and milk during lactation and in plasma of suckling neonates. The present study is a continuation of previous ones using the same treatment protocol in pregnant sows where it was found that with the exception of a slightly improved growth performance in offspring of FO fed sows, no difference was found in reproductive performance between the two groups [22][23][24][25].…”
Section: Introductionsupporting
confidence: 67%